Revisiting the History of One Manuscript Book Issued by Emigrant Kalmyks in 1947 - A. Bayanova (Монголоведение, 2019)
The article examines one rare manuscript book which is a school primer for children of emigrant Kalmyks that resided in Pfaffenhofen DP Camp (Germany) in the late 1940s. The paper analyzes and describes the book in detail, special attention being paid to its design and contents. The surviving copy of the primer reveals an important aspect of educational practices in the history of emigration of different peoples within DP camps and during the early years of their permanent residence in respective countries that hosted multi-ethnic expatriate groups in the aftermath of World War II.